2012
DOI: 10.1021/cg3005689
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring of Stirring Effects on Polymorphic Transformations during Cooling Crystallization of Carbamazepine

Abstract: The influence of experimental conditions on polymorphic outcome and transformations during cooling crystallization of carbamazepine (CBZ) from anhydrous ethanol has been investigated. Stirring was found to be the most important controlling factor for the initial polymorphic outcome in solutions prepared using commercial CBZ powder. For quiescent conditions, a few large crystals of the metastable trigonal α form (II) initially appeared, undergoing subsequent slow transformation into the stable P-monoclinic β fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…The effect of stirring on m-hydroxybenzoic acid solutions found that the proportion of the stable form decreases under intermediate agitation rates, accompanied by a large reduction in nucleation time of the metastable form. 7 The effect of stirring conditions on cooling crystallisation of carbamazepine from anhydrous ethanol was investigated by Sypek et al 8 In this study, crystals of form II were formed and then slowly transformed to crystals of form III under quiescent conditions. In the case of sufficiently vigorous stirring, the induction times observed were clearly defined by the onset of turbidity which was due to formation of a large number of small form III crystals.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The effect of stirring on m-hydroxybenzoic acid solutions found that the proportion of the stable form decreases under intermediate agitation rates, accompanied by a large reduction in nucleation time of the metastable form. 7 The effect of stirring conditions on cooling crystallisation of carbamazepine from anhydrous ethanol was investigated by Sypek et al 8 In this study, crystals of form II were formed and then slowly transformed to crystals of form III under quiescent conditions. In the case of sufficiently vigorous stirring, the induction times observed were clearly defined by the onset of turbidity which was due to formation of a large number of small form III crystals.…”
Section: Introductionmentioning
confidence: 94%
“…However, there are numerous examples where agitation plays profound role in determining polymorphic outcome in crystallisation of pharmaceuticals and other molecular systems, such as carbamazepine, stearic acid, L-glutamic acid, m-hydroxybenzoic acid 7 or glycine. [8][9][10][11] In industrial applications it is vital to understand the impact of process conditions such as agitation on polymorphism in order to scale up crystallisation processes properly accounting for differences in agitation between labbased, pilot scale and plant scale processes.…”
Section: Introductionmentioning
confidence: 99%
“…CBZ is a drug that used as anticonvulsant for treatment of epilepsy and trigeminal neuralgia [14]. CBZ can be classified in class 2 drugs under biopharmaceutics classification system (BCS) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Since the conformation and packing of molecules in solution directly depended on the fluid hydrodynamic in crystallizer, the fluid hydrodynamic is certainly considered as the key factor to control the selective and phase transformation of polymorphism [7][8][9]. For example, Sypek et al [7] reported that the stable phase of carbamazepine was selectively obtained in stirred crystallization, whereas the unstable phase was preferably crystallized in a stagnant crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Since the conformation and packing of molecules in solution directly depended on the fluid hydrodynamic in crystallizer, the fluid hydrodynamic is certainly considered as the key factor to control the selective and phase transformation of polymorphism [7][8][9]. For example, Sypek et al [7] reported that the stable phase of carbamazepine was selectively obtained in stirred crystallization, whereas the unstable phase was preferably crystallized in a stagnant crystallization. As regards the phase transformation, Davey et al [8] indicated that the completed phase transformation of 2,6dihydroxybenzoic acid from unstable to stable phase required at least 20 days in a stagnant crystallization, but it was significantly reduced to only 2−3 days in stirred crystallization.…”
Section: Introductionmentioning
confidence: 99%